Analisis Pengaruh Penambahan Jumlah Bilah Turbin Angin Terhadap Torsi dan Daya Pada Airfoil NACA 0018 - Pakpahan, Efendi Alvonco; Kardiman; Iwan Nugraha Gusniar (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
This study aims to analyze the effect of increasing the number of blades on a vertical axis wind turbine on the torque and power generated using the NACA 0018 airfoil. The need for efficient and sustainable renewable energy sources underscores the importance of wind turbines in the energy sector. In wind turbine design, the number of blades is a critical factor that influences the turbine's performance and efficiency. Therefore, this research focuses on understanding how variations in the number of blades affect key performance parameters such as torque and power. Simulations were conducted using ANSYS software at wind speeds of 3 m/s, 5 m/s, and 8 m/s over 10 seconds, testing blade configurations of 2, 3, 4, and 5 blades. At 3 m/s and 5 m/s, the three-blade turbine produced the highest torque and power, with maximum values of 0.358271 Nm and 5.0073110 W at 3 m/s, and 0.99525 Nm and 20.83626 W at 5 m/s.At high wind speeds (8 m/s), the two-blade turbine showed excellent performance with a maximum torque of 1.806616 Nm and maximum power of 38.36925 W. The five-blade turbine had stable performance across all wind speeds but came with higher production and maintenance costs. The four-blade turbine offered intermediate performance, better than the two-blade but less efficient than the three-blade setup. This study concludes that the three-blade turbine is most efficient for low to medium wind speeds, while the two-blade turbine performs best at high wind speeds.